The Influence Of Audit Firm Size, Leverage, And Disclosure On Going Concern Audit Opinions - Adinda Zahwa Cynthia Andhanie; Ni Nyoman Alit Triani (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Examining how audit firm size, leverage, and disclosure affect the issuing of going-concern audit opinions across sector-wide corporations listed on the Indonesia Stock Exchange during the year 2021 is the main goal of this study (IDX). This research adopts a quantitative methodology, incorporating three independent variables, specifically audit firm size, leverage, and voluntary disclosure levels, while the issue of going-concern audit opinions is the dependent variable under consideration. The results of the investigation show that the size of the audit firm has a favorable effect on the chance of issuing a going-concern opinion. Conversely, the leverage of the company does not show a statistically significant impact on whether going-concern opinions are issued. Furthermore, it is discovered that there is a bad correlation between the level of disclosure and the inclination to provide going-concern audit opinions.